PRELIMINARY STUDY OF THE POLLEN MORPHOLOGY OF MALAYSIAN ZINGIBERACEAE (TRIBE ALPINIEAE) AND THE TAXONOMIC RELATIONSHIP - Mohamad, Salasiah; Kalu, Meekiong; Sedek, Aimi Syazana (Research Center for Biology, 2023)
The family Zingiberaceae forms an important herbaceous layer in the tropical forests of Malaysia. From a phylogenetic point of view, certain genera of the problematic tribe Alpinieae are non-monophyletic and in need of more taxonomic evidence to support the classification. This study demonstrates how the palynological data could correlate with the proposed phylogenetic data, using representatives from the Malaysian species. The pollen morphology of 21 species from the tribe Alpinieae was investigated. Parameters including polarity, symmetry, shape, size, apertures, exine ornamentation, size of spine, type of spine apex, spine density, and distance between spine were analysed. The results demonstrated that the studied species were conveniently divided into two major groups based on the exine sculpturing of the spheroidal pollens, either psilate as in Etlingera and Hornstedtia, or echinate as in Alpinia, Conamomum, Meistera, Plagiostachys, Sundamomum, and Sulettaria. Hence, as far as the study is concerned, the main sculpturing is considered useful to generally distinguish the genera in the tribe.